High-Resolution Numerical Modeling of Barotropic Global Ocean Tides for Satellite Gravimetry - Sulzbach, Roman; Dobslaw, H.; Thomas, Maik (Freie Universität Berlin, 2021)
The recently upgraded barotropic tidal model TiME is employed to study the influence of fundamental tidal processes, the chosen model resolution, and the bathymetric map on the achievable model accuracy, exemplary for the M2 tide. Additionally, the newly introduced pole-rotation scheme allows to estimate the model’s inherent precision (open ocean rms: 0.90 cm) and enables studies of the Arctic domain without numerical deviations originating from pole cap handling. We find that the smallest open ocean rms with respect to the FES14-atlas (3.39 cm) is obtained when tidal dissipation is carried out to similar parts by quadratic bottom friction, wave drag, and parametrized eddy-viscosity. This setting proves versatile to obtaining high accuracy values for a diverse ensemble of additional partial tides. Using the preferred model settings, we show that for certain minor tides it is possible to obtain solutions that are more accurate than results derived with admittance assumptions from data-constrained tidal atlases. As linear admittance derived minor tides are routinely used for de-aliasing of satellite gravimetric data, this opens the potential for improving gravity field products by employing the solutions from TiME.